Systematic Study of the Stereoelectronic Properties of Trifluoromethylated Triarylphosphines and the Correlation of their Behaviour as Ligands in the Rh‐Catalysed Hydroformylation. Issue 4 (29th December 2020) - Herrera, Daniel; Peral, Daniel; Cordón, Mercedes; Bayón, J. Carles
Abstract: The stereoelectronic properties of a series of trifluoromethylated aromatic phosphines have been studied using different approaches. The σ‐donating capability has been evaluated by nuclear magnetic resonance (NMR) spectroscopy of the selenide derivatives and the protonated form of the different trifluoromethylated phosphines. The coupling constants between phosphorous and selenium ( 1 JSeP ) and phosphorous and hydrogen ( 1 JHP ) can be predicted by empirical equations and correlate the basicity of the phosphines with the number and relative position of trifluoromethyl groups. In contrast, the π‐acceptor character of the ligands has been evaluated by measuring the frequency of the CO vibration in the infrared (IR) spectra of the corresponding Vaska type iridium complexes ([IrCl(CO)(PAr3 )2 ], PAr3 =triarylphosphine). Moreover, the correlation between the electronic properties and the performance of these phosphines as ligands in the rhodium‐catalysed hydroformylation of 1‐octene has been established. Phosphines with the lowest basicity, that are those with the highest number of trifluoromethyl groups, gave rise to more active catalytic systems. Abstract : The σ‐donating and the π‐acceptor character of a series of trifluoromethylated phosphines have been evaluated using the selenide and phosphonium derivatives and the corresponding Vaska type iridium complexes ([IrCl(CO)(PAr3 )2 ], PAr3 =triarylphosphine), respectively. The stereoelectronic properties have been correlated with the performance of these ligands in the rhodium catalysed hydroformylation of 1‐octene.